2009
DOI: 10.1371/journal.pgen.1000635
|View full text |Cite|
|
Sign up to set email alerts
|

GASZ Is Essential for Male Meiosis and Suppression of Retrotransposon Expression in the Male Germline

Abstract: Nuage are amorphous ultrastructural granules in the cytoplasm of male germ cells as divergent as Drosophila, Xenopus, and Homo sapiens. Most nuage are cytoplasmic ribonucleoprotein structures implicated in diverse RNA metabolism including the regulation of PIWI-interacting RNA (piRNA) synthesis by the PIWI family (i.e., MILI, MIWI2, and MIWI). MILI is prominent in embryonic and early post-natal germ cells in nuage also called germinal granules that are often associated with mitochondria and called intermitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
169
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(184 citation statements)
references
References 75 publications
5
169
0
Order By: Relevance
“…TE reactivation also perturbs the self-renewal program of spermatogonial stem cells, which results in spermatogenic tubules completely devoid of any germ cells within a few weeks. This phenotype was originally described for the methylationdeficient Dnmt3L mutant males (Bourc'his and Bestor, 2004), observed again in PIWI mutants (Carmell et al, 2007;Aravin et al, 2007b) and more recently recapitulated in mutations for proteins supporting the piRNA/ PIWI pathway, such as the Tudor domain-containing proteins TDRD1 and TDRD9 (Ollinger et al, 2008;Soper et al, 2008;Ma et al, 2009;Reuter et al, 2009;Shoji et al, 2009). Tudor domain-containing proteins assemble specialized RNA processing platforms in the cytoplasm of germ cells, to which they recruit PIWI proteins through their ability to bind symmetrically dimethylated arginines, a post-translational modification undergone by both MILI and MIWI2 (Aravin et al, 2009;Vagin et al, 2009;Wang et al, 2009;Shoji et al, 2009).…”
Section: Te Silencing In the Germlinementioning
confidence: 66%
See 2 more Smart Citations
“…TE reactivation also perturbs the self-renewal program of spermatogonial stem cells, which results in spermatogenic tubules completely devoid of any germ cells within a few weeks. This phenotype was originally described for the methylationdeficient Dnmt3L mutant males (Bourc'his and Bestor, 2004), observed again in PIWI mutants (Carmell et al, 2007;Aravin et al, 2007b) and more recently recapitulated in mutations for proteins supporting the piRNA/ PIWI pathway, such as the Tudor domain-containing proteins TDRD1 and TDRD9 (Ollinger et al, 2008;Soper et al, 2008;Ma et al, 2009;Reuter et al, 2009;Shoji et al, 2009). Tudor domain-containing proteins assemble specialized RNA processing platforms in the cytoplasm of germ cells, to which they recruit PIWI proteins through their ability to bind symmetrically dimethylated arginines, a post-translational modification undergone by both MILI and MIWI2 (Aravin et al, 2009;Vagin et al, 2009;Wang et al, 2009;Shoji et al, 2009).…”
Section: Te Silencing In the Germlinementioning
confidence: 66%
“…Tudor domain-containing proteins assemble specialized RNA processing platforms in the cytoplasm of germ cells, to which they recruit PIWI proteins through their ability to bind symmetrically dimethylated arginines, a post-translational modification undergone by both MILI and MIWI2 (Aravin et al, 2009;Vagin et al, 2009;Wang et al, 2009;Shoji et al, 2009). As a whole, directed mutagenesis in mice has allowed the identification of nine proteins with a key role in safe guarding the male germline against TEs (Table 1 and Figure 1): Dnmt3L, Dnmt3A, MIWI2, MILI, Maelstrom (MAEL), TDRD1, TDRD9, GASZ and Tex19.1 (Testis expressed 19.1) (Ollinger et al, 2008;Soper et al, 2008;Ma et al, 2009). All of these proteins, except Tex19.1, have been involved in the same TE restricting pathway, initiated by Figure 1 Expression pattern and mutant phenotype of proteins involved in TE repression in the developing male germline in mice.…”
Section: Te Silencing In the Germlinementioning
confidence: 99%
See 1 more Smart Citation
“…The murine transposon-derived piRNAs share features with the Drosophila repeat-associated piRNAs and are also proposed to control transposable elements (Klattenhoff and Theurkauf 2008). In addition to PIWI proteins, other proteins such as GASZ, MOV10L1, Sun1, Tdrd9, and Tdrd1 are also required for biogenesis and/or stability of mouse piRNAs (Chi et al 2009;Ma et al 2009;Reuter et al 2009;Shoji et al 2009;Zheng et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that a Tudor domain-containing (Tdrd) protein known as Tdrkh promotes the 3 ′ trimming process (Honda et al 2013;Saxe et al 2013). In addition to Piwi proteins and Zuc, other factors essential for piRNA processing, including GASZ (germ cell protein with ankyrin repeats, sterile α motif, and leucine zipper) and Tdrd proteins (Hosokawa et al 2007;Ma et al 2009), are localized on the cytoplasmic surface of mitochondria in electron-dense granules known as intermitochondrial cement (ICM) in mammalian spermatocytes or more generally as nuage in Drosophila and other animals (Siomi et al 2011;Pillai and Chuma 2012).…”
mentioning
confidence: 99%